Adaptação de impressora convencional para confecção de circuitos de nanopartículas de prata - Aguiar, Wagner Mendonça Alves (2018)
The search for new technologies implementation on a large scale aiming the production cost reduction have been a trend. In this way, this work proposes to adapt a conventional printer looking for the obtaining of low cost electronics circuits with potential application as a soil moisture and temperature sensor. To obtaining the circuits the inkjet printing technique was used due it allows the fast prototyping and large scale fabrication of functional. To realize the adaptation, a Brother DCP-T300™ printer was chosen a taking into account the maximum resolution and the printer head type. The silver nanoparticles ink selection as the printing fluid occurred analyzing the most suitable viscosity to inkjet printing, its resistivity and its resistance to oxidation. As adopted circuitry geometry the interdigitated electrodes (IDE) was chosen due its simplicity and the possibility of integration to moisture and temperature sensors. Then, the most suitable printing parameters were set and the influence of the spacing between the electrodes, of its width, of its substrate and of the drying environment on the electrical resistance was investigated. The electric resistance along the trails and the microscopy indicated that the printed circuits in photographic paper, with 300 μm spacing between electrodes and 300 μm and 500 μm width, dried on environment presented the most suitable proprieties. In the electric resistance variation analysis versus temperature, in the zone between -20°C and 50°C, the circuits of 300 μm width indicated higher sensibility, potentially been useful in the zone between 0°C and 40°C. Therefore, the conventional printer adaptation has showed up promising to obtain circuits with potential to moisture sensing, being a low cost and simplified methodology.